Effect of closing material on hearing rehabilitation in stapedectomy and stapedotomy: A finite element analysis - Lim, Jongwoo; Goo, Woonhoe; Kang, Dae Woong; Oh, Seung Ha; Kim, Namkeun (Frontiers in Neuroscience, 2023)
Stapedotomy or stapedectomy operations are often performed to treat otosclerosis. During the operation, the space created by bone removal is usually filled with a closing material such as fat or fascia. In this study, the effect of the Young’s modulus of the closing material on the hearing level was investigated through the 3D finite element model of a human head including auditory periphery. The Young’s moduli of the closing material used to implement stapedotomy and stapedectomy conditions in the model were varied from 1 kPa to 24 MPa. The results showed that the hearing level improved when the closing material was more compliant after stapedotomy. Therefore, when the stapedotomy was performed using fat whose Young’s modulus is lowest among the potential closing materials, the hearing level recovered the best among all simulated cases. On the other hand, in stapedectomy, the Young’s modulus did not have the linear relationship between the hearing level and the compliance of the closing material. Hence, the Young’s modulus causing the best hearing rehabilitation in stapedectomy was found not at the end of the investigated range of Young’s modulus but somewhere in the middle of the given range.